Mini-laparoscopy, laparoendoscopic single-site surgery and natural orifice transluminal endoscopic surgery-assisted laparoscopy : novice surgeons’ performance and perception in a porcine nephrectomy model - Autorino, Riccardo (2012)
Study Type--Therapy (case series) Level of Evidence 4. What's known on the subject? and What does the study add? Over the last few years, minimally invasive urological surgery has evolved towards less invasive, 'scarless' procedures. New surgical concepts, such as those of natural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) have been introduced. Mini-laparoscopy has been rediscovered in an attempt to reduce the invasiveness of standard laparoscopy. This study is the first to compare the perception of surgeons when first facing three different scarless options for performing a porcine nephrectomy and when dealing with the constraints of each technique. The study findings suggest that: (i) when first approaching these techniques, surgeons tend to perform equally well under expert guidance in the porcine model; (ii) mini-laparoscopy is perceived as less difficult to perform; (iii) for all the techniques, surgeon's impressions are in line with their expectations. OBJECTIVE: • To evaluate the perception and performance of urological surgeons when first applying scarless surgical techniques. METHODS: • The study was conducted during the 2(nd) Minimally Invasive Urological Surgical Week annual course in Braga, Portugal. • Fourteen attendees performed three porcine nephrectomies by using each of the following techniques: mini-laparoscopy, laparoendoscopic single-site surgery (LESS) and natural orifice transluminal endoscopic surgery (NOTES)-assisted laparoscopy. • Peri-operative data were recorded, and operating performance was scored by one experienced surgeon for each working station, using a global rating scale. • The surgeons' subjective perceptions of degree of difficulty were graded and their expectations before the procedures were recorded. RESULTS: • Forty-two porcine nephrectomies were performed. • There were no differences in overall operating time, or time to dissect and manage the renal vascular hilum, whereas time to gain access was faster for LESS than for mini-laparoscopy or NOTES-assisted laparoscopy (mean [sd] 8 [6] min vs 10.2 [5.3] min vs 9.9 [5.3] min, respectively; P = 0.59). • A better visualization of the surgical field was obtained with mini-laparoscopy and there was a higher degree of difficulty of bimanual dexterity for LESS, but no significant differences were found among the three techniques for any variable (operating field view: P = 0.52; bimanual dexterity: P = 0.49; efficiency: P = 0.77; tissue handling: P = 0.61; autonomy: P = 0.2). • Subjective perception of the degree of difficulty trended in favour of mini-laparoscopy (P= 0.17), but no significant difference was found in terms of surgeons' impression as compared with their expectations (P = 0.34). CONCLUSIONS: • When first approaching new scarless techniques, surgeons tend to perform equally well under expert guidance in the porcine model. • Mini-laparoscopy is perceived as less difficult to perform and, for all the techniques, surgeons' impressions are in line with their expectations.